Prevalence of hepatitis C virus and human immunodeficiency virus in a group of patients newly diagnosed with active tuberculosis in Porto Alegre, Southern Brazil - Cintia Costi; Tarciana Grandi; Maria Laura Halon; Márcia Susana Nunes Silva; Cláudia Maria Dornelles da Silva; Tatiana Schäffer Gregianini; Lia Gonçalves Possuelo; Carla Adriane Jarczewski; Christian Niel; Maria Lucia Rosa Rossetti (Memorias do Instituto Oswaldo Cruz)
BACKGROUND Porto Alegre is the Brazilian state capital with second highest incidence of tuberculosis (TB) and the highest proportion of people infected with human immunodeficiency virus (HIV) among patients with TB. Hepatitis C virus (HCV) infection increases the risk of anti-TB drug-induced hepatotoxicity, which may result in discontinuation of the therapy. OBJECTIVES The aim of this study was (i) to estimate prevalence of HCV and HIV in a group of patients newly diagnosed with active TB in a public reference hospital in Porto Alegre and (ii) to compare demographic, behavioural, and clinical characteristics of patients in relation to their HCV infection status. METHODS One hundred and thirty-eight patients with TB were tested for anti-HCV antibody, HCV RNA, and anti-HIV1/2 antibody markers. HCV RNA from real-time polymerase chain reaction (PCR)-positive samples was submitted to reverse transcription and PCR amplification. The 5′ non-coding region of the HCV genome was sequenced, and genotypes of HCV isolates were determined. FINDINGS Anti-HCV antibody, HCV RNA, and anti-HIV antibodies were detected in 27 [20%; 95% confidence interval (CI), 13-26%], 17 (12%; 95% CI, 7-18%), and 34 (25%; 95% CI, 17-32%) patients, respectively. HCV isolates belonged to genotypes 1 (n = 12) and 3 (n = 4). Some characteristics were significantly more frequent in patients infected with HCV. Among them, non-white individuals, alcoholics, users of illicit drugs, imprisoned individuals, and those with history of previous TB episode were more commonly infected with HCV (p < 0.05). MAIN CONCLUSIONS HCV screening, including detection of anti-HCV antibody and HCV RNA, will be important to improving the management of co-infected patients, given their increased risk of developing TB treatment-related hepatotoxicity.